The greedy unicorn: Airbnb and capital concentration in 12 European cities - Anselmi, Guido; Chiappini, Letizia; Prestileo, Federico (City, culture and society, 2021)
Despite discourses on how digital platforms have democratized access to the market there is increasing evidence on their role in boosting concentration, as recommender algorithms and digital reputation tools usually favour a small clique of top users, this may include short term rental platforms. There is also mounting evidence regarding the production of negative externalities connected to the proliferation of Airbnb (and similar services). Our contribution investigates the political economy of concentration in Airbnb leveraging the lens of urban studies while problematizing digital platforms as key contemporary infrastructures. Using a dataset of 6,5 million reviews from Inside Airbnb we estimate a) yearly revenue and listing concentration b) the proportion of listings which are more likely to feed negative externalities in the housing sector eg. those listing full houses and those having high availability in twelve European cities. Starting from a simple measure of a phenomenon that has hardly been quantized in recent literature, we dissect the role of STR platforms in urban political economy. •Short term rental platforms generate a ‘rich get richer’ effect.•This is totally unregulated at the local or translocal level.•local economic context seems to make no difference.•Short term rental platforms are a new form of footloose capital.•Upscaling of regulation may be required.